BLADE Sequences in Transverse T2-weighted MR Imaging of the Cervical Spine. Cut-off for Artefacts? - Finkenzeller, T.; Wendl, C. M.; Lenhart, S.; Stroszczynski, C.; Schuierer, G.; Fellner, C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: The BLADE (PROPELLER) technique reduces artefacts in imaging of the cervical spine in sagittal orientation, but till now failed to do so in axial orientation, because here it increased through plane CSF-flow artefacts, which spoiled the benefit of BLADE artefact reduction “in plane”. The aim of this study was to compare a BLADE sequence with optimised measurement parameters in axial orientation to T2-TSE.Materials and Methods: Both sequences were compared in 58 patients with 31 discal, 16 bony and 11 spinal cord lesions. Image sharpness, reliability of spinal cord depiction, CSF flow artefacts and lesion detection were evaluated by 3 independent observers. Additionally the observers were asked which sequence they would prefer for diagnostic workup. Statistical evaluations were performed using sign and χ2 test.Results: BLADE was significantly superior concerning image sharpness, spinal cord depiction and overall lesion detection. BLADE was rated better for most pathologies, for bony lesions the differences compared with TSE were statistically significant. Regarding CSF-flow artefacts both sequences showed no difference. All readers preferred BLADE in side by side reading.Conclusion: An optimised axial T2 BLADE sequence decreases the problems of increased through plane CSF-flow artefacts in this orientation. By reducing various other artefacts it yields better image quality and has the potential to reduce the number of non-diagnostic examinations especially in uncooperative patients.Key points:• T2 BLADE/PROPELLER sequences proofed to reduce artefacts in sagittal spine imaging• BLADE/PROPELLER improve image quality, but can aggravate CSF flow artefacts in axial orientation• optimised parameter setting for axial T2 BLADE reduces “through-plane” CSF artefacts aggravation• optimised axial T2 BLADE reduces non-diagnostic examinations especially in uncooperative patientsCitation Format:• Finkenzeller T, Wendl CM, Lenhart S et al. BLADE Sequences in Transverse T2-weighted MR Imaging of the Cervical Spine. Cut-off for Artefacts?. Fortschr Röntgenstr 2015; 187: 102 – 108
Keywords: spine; spinal cord; MR-imaging; spinal canal; technical aspects